PEMODELAN ANOMALI GRAVITASI DENGAN PENDEKATAN BENDA BERBENTUK SILINDER - Rahmanto, Dedi; Yulianto, Tony (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT—A gravity anomalies modeling program has been made with the approximation of cylinder shaped body for the case of N anomalous bodies. This program is named DRAVECT version 1.1. The modeling program was executed by Microsoft Visual Basic 6.0 programming language.The program was made by identifying gravity problems. Input and output data that be identified from gravity parameters, dimension and position parameters of anomalous bodies. The gravity anomalies were calculated by inserting synthetic data to the modeling program. The anomaly profiles 3 D were displayed automatically, and the profiles of gravity anomalies 2 D were made respectively. Validation test had been done by compare program result with reference. Based on the graphical qualitative interpretation of gravity anomaly profiles as the result of the conducted modeling, it was obtained the characteristics of gravity anomaly of cylinder shaped body. Keyword : gravity anomalies, cylinder